STRATEGI PENGHINDARAN PAJAK: DAMPAKNYA TERHADAP BIAYA UTANG DAN IMPLIKASI AUDIT - Firmansyah, Amrie; Santoso, Agnes Novita Mega Putri (Politeknik Keuangan Negara STAN, 2024)
This study aims to analyze the effect of tax avoidance on the cost of debt and the moderating role of audit quality in this relationship for manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2022 period. The sample consisted of 22 manufacturing companies selected using purposive sampling, resulting in a total of 66 observations over three years of observation. This research employs a quantitative approach using secondary data from the companies' financial statements, analyzed with multiple linear regression. Tax avoidance was measured using the Effective Tax Rate (ETR) proxy multiplied by -1, while audit quality was measured based on whether the financial statements were audited by Big Four Public Accounting Firms. The results show that tax avoidance has a significant negative effect on the cost of debt, indicating that tax avoidance strategies can help companies reduce their cost of debt. However, audit quality does not moderate the relationship between tax avoidance and the cost of debt. These findings contribute to the financial accounting literature by highlighting the role of tax management in mitigating debt costs while providing recommendations to regulators to improve regulations related to tax avoidance and debt cost transparency.